EQUITABLE BUDGETARY ALLOCATION: A CATALYST FOR ACHIEVING NATIONAL DEVELOPMENT OF NIGERIA - Saifullahi Sani Ibrahim; Abubakar Muhammad Ahmad (European Scientific Journal, ESJ, 2013)
Fiscal federalism compelled state and local governments to heavily rely on monthly subvention from the federal government to cover their cost of both day to day and long term financial needs. The present arrangement of the revenue distribution formula laid much emphasis on the revenue derivation (revenue source) at the expenses of the financial needs of the state and local government. This subjected most of the states in the northern part of Nigeria to receive very little in spite been relatively densely populated compared with the other geopolitical regions. The repercussion of the foregoing is a massive proliferation of poor more especially in the northern-eastern geopolitical zone. This study critically examines the effect of budgetary allocation of national development. It was found in this paper that skewed budgetary allocation causes unbalance development leading to economic underdevelopment in the northern part of the country. The paper concludes that for Nigeria to achieve holistic national development, resources must be equitably distributed. Specifically, we recommend inward-looking policies that could absorb the bunch of unemployed youth thereby enabling them to contribute their quota toward achieving national development shall be rigorously initiated and vigorously implemented.